Comparison of Pipette and Laser Diffraction Methods in Determining the Granulometric Content of Fluvial Sediment Samples - Kun, Ágnes; Katona, Orsolya; Sipos, György; Barta, Károly (Journal of Environmental Geography, 2013)
Nowadays there is a growing demand for rapid and accurate determination of grain size distribution. The conventional pipette method is time-consuming and provides less detailed data compared to recently introduced methods. However, in Hungarian practice the pipette method is still considered to be the standard one, as there are a long series of measurements, and grain size thresholds used in sedimentology and soil sciences are based on this approach. The aim of our research was to determine the comparability of the laser diffraction method (LDM) with the conventional pipette method (PM), in order to investigate the controversial question on the interchangeability of the two methods. Based on our measurements on some representative fluvial sediment samples, we found that the largest difference in results can be expected in the silty grain size range. However if the main fractions (clay, silt, sand) are considered the methods provided similar very results, and correlation factors were above 0.92. In all, the LDM has a clear advantage because of its speed, reproducibility and fewer possibilities for operator failure.